How intron splicing affects the deletion and insertion profile in Drosophila melanogaster. - Ptak, S.E.; Petrov, D.A. (Genetics, 2002)
Studies of "dead-on-arrival" transposable elements in Drosophila melanogaster found that deletions outnumber insertions approximately 8:1 with a median size for deletions of approximately 10 bp. These results are consistent with the deletion and insertion profiles found in most other Drosophila pseudogenes. In contrast, a recent study of D. melanogaster introns found a deletion/insertion ratio of 1.35:1, with 84% of deletions being shorter than 10 bp. This discrepancy could be explained if deletions, especially long deletions, are more frequently strongly deleterious than insertions and are eliminated disproportionately from intron sequences. To test this possibility, we use analysis and simulations to examine how deletions and insertions of different lengths affect different components of splicing and determine the distribution of deletions and insertions that preserve the original exons. We find that, consistent with our predictions, longer deletions affect splicing at a much higher rate compared to insertions and short deletions. We also explore other potential constraints in introns and show that most of these also disproportionately affect large deletions. Altogether we demonstrate that constraints in introns may explain much of the difference in the pattern of deletions and insertions observed in Drosophila introns and pseudogenes.